Anthocyanin-rich blue potato meals protect against polychlorinated biphenyl-mediated disruption of short-chain fatty acid production and gut microbiota profiles in a simulated human digestion model - Lu, Fang; MacPherson, Chad W.; Tremblay, Julien; Iskandar, Michèle M.; Kubow, Stan (Frontiers in Nutrition, 2023)
Background: Polychlorinated biphenyls (PCBs) are ubiquitous environmental pollutants associated with a wide variety of adverse human health outcomes. PCB 126 and PCB 153 are among the most prevalent congeners associated with human exposure. Emerging studies have suggested that PCB exposure leads to lower gut microbial diversity although their effects on microbial production of health promoting short-chain fatty acids (SCFAs) has been scarcely studied. Blue potatoes are rich in anthocyanins (ACNs), which is a class of polyphenols that promote the growth of beneficial intestinal bacteria such as Bifidobacterium and Lactobacillus and increase the generation of SCFAs. A batch-culture, pH-controlled, stirred system containing human fecal microbial communities was utilized to assess whether human gut microbiota composition and SCFA production are affected by: (a) PCB126 and PCB153 exposure; and (b) ACN-rich digests in the presence and absence of the PCB congeners. Methods: ACN-rich blue potato meals were digested over 12 h with and without PCB 126 and PCB 153 using an in vitro simulated gut digestion model involving upper gastrointestinal digestion followed by metabolism by human fecal microbiota. Fecal digests were collected for analysis of gut microbial and SCFA profiles. Results: PCB-exposed fecal samples showed a significant (p<0.05) decrease in species richness and a significantly (p<0.05) different microbial community structure. PCB treatment was associated with an increased (p<0.05) relative abundance of Akkermansia, Eggerthella and Bifidobacterium and a decreased (p<0.05) relative abundance of Veillonella, Streptococcus and Holdemanella. ACN digests counteracted the altered abundances of Akkermansia and Bifidobacterium seen with the PCB treatment. PCB exposure was associated with a significant (p<0.05) decrease in total SCFA and acetate concentrations. ACN digests were associated with significantly (p<0.05) higher SCFA and acetate concentrations in the presence and absence of PCBs. Conclusion: Human fecal matter exposed to PCB 126 and PCB 153 led to decreased abundance and altered gut microbiota profiles as well as lowered SCFA and acetate levels. Importantly, this study showed that prebiotic ACN-rich potatoes counteract PCB-mediated disruptions in human gut microbiota profiles and SCFA production.